HOMEOPATHIC TREATMENT AS AN APPROACH TO DIABETES AND HYPERTENSION (Cadernos ESP, 2022)
This article aims to present the experience of a municipality in Ceará regarding homeopathic treatment, as a new approach to cases of diabetes and hypertension, with a view to reducing the impact of municipal indicators of diseases, and improving the quality of life of users. It was conducted using the inclusion criterion: living in the area of the team, being hypertensive and/or diabetic, and for the exclusion criterion: lack of interest in doing homeopathic treatment. Resulting in the Caiçara team a population with the lowest percentage of diabetics and hypertensive in the municipality. In the final period of this practice (August to November 2021) 4.44% of this population was identified with diabetes and 7.91% with hypertension, in addition to being the one that least uses medicines for these pathologies. It is concluded that in this population it was possible to observe evident advantages in the treatment, better results in health indicators, as well as a reduction in the consumption of conventional medicines for the treatment of diabetes and hypertension.
Keywords: Homeopathy; Diabetes Mellitus; Hypertension